Modelagem matemática nos anos 1980: narrativas e itinerários de cursos de especialização - Fillos, Leoni Malinoski [UNESP] (Universidade Estadual Paulista (Unesp), 2019)
Esta pesquisa teve por objetivo analisar a dinâmica de idealização e desenvolvimento dos primeiros cursos de especialização com ênfase na Modelagem Matemática, realizados na década de 1980, e as correlações entre tais cursos e a constituição da Educação Matemática no espaço acadêmico-científico brasileiro. De forma mais específica, buscamos interpretar e discutir as experiências pessoais relatadas por professores envolvidos com os primeiros cursos realizados na Fundação Faculdade de Filosofia, Ciências e Letras de Guarapuava (Fafig), e investigar os enraizamentos e relações desses cursos com outros realizados posteriormente no Brasil. Empreendemos, para tanto, uma pesquisa de caráter qualitativo e optamos pela metodologia da História Oral, conforme a concebemos e praticamos no Grupo de História Oral e Educação Matemática (Ghoem). Os procedimentos metodológicos nos possibilitaram criar onze narrativas a partir de entrevistas realizadas com doze professores, gestores dos cursos ou responsáveis por ministrar as disciplinas, além de mobilizar fontes escritas encontradas em arquivos, como cronogramas, relatórios e ementas. A análise dos dados nos possibilitou elaborar três narrativas históricas que abordam: (i) o contexto de criação e desenvolvimento da Fundação Faculdade de Filosofia, Ciências e Letras de Guarapuava e como os cursos de especialização ofertados nessa instituição se inserem nessa conjuntura; (ii) os movimentos e práticas em torno de uma nova proposta, a Modelagem Matemática, nos cursos de especialização; (iii) as implicações dos cursos de especialização para o Programa de Pós-Graduação em Educação Matemática de Rio Claro e, por extensão, para a constituição da Educação Matemática brasileira.

The purpose of this research is to analyse the earliest academic specialisation courses with an emphasis on Mathematical Modelling, chiefly in what concerns their dynamics of idealisation and development. Furthermore, the study investigates what the correlations that may be identified between such coursesare, dating back to 1980, as well as the constitution of Mathematics Education within the Brazilian academic and scientific locus. More specifically, the research is an endeavour to interpret and discuss the personal experiences that have been reported by professors somehow involved in the first courses that have been taught in the Fundação Faculdade de Filosofia, Ciências e Letras de Guarapuava (Fafig) – Guarapuava (Paraná, Brazil) Philosophy, Sciences, and Languages College Foundation. Thereby, it is possible to examine the relations and interconnections of the aforementioned courses with the ones that have been taught subsequently in Brazil. As for the operational basis of this undertaking, the choice has been for a qualitative research, as well as for the Oral History Methodology, in coherence with the way it is conceived and practiced within the Grupo de História Oral e Educação Matemática (Ghoem) – Mathematics Education and Oral History Research Group. As a result, the methodological procedures have allowed written sources found in archives, such as schedules, reports, and syllabi, to be mobilised. Moreover, eleven narratives could also be created, emerging from interviews carried out with twelve professors. The participants are all managers and/or responsible for the courses that are taught. Data analysis has given an opportunity for the study to elaborate upon three historical narratives that address: (i) in which context the surfacing, shaping, and development of the Fundação Faculdade de Filosofia, Ciências e Letras de Guarapuava has taken place, as well as the manner whereby the specialisation courses provided by this institution are inserted within such conjuncture; (ii) the movements and practices that encompass this new proposal, Mathematical Modelling, throughout the specialisation courses; and (iii) the implications of these specialisation courses for the Rio Claro Postgraduate Programme on Mathematics Education (PR, Brazil) and, accordingly, for the constitution of Brazilian Mathematics Education on the whole.
Mathematical modeling in the 1980’s: narratives and itineraries of specialization courses
Keywords: História da Educação Matemática; Cursos de especialização; Faculdade de Filosofia, Ciências e Letras de Guarapuava; História oral; Mathematics education history; Specialisation courses; Guarapuava (Paraná, Brazil) Philosophy, Sciences, and Languages College Foundation; Oral history